ANALISIS POLA KOMUNIKASI ORANG TUA DENGAN ANAK REMAJA LAKI-LAKI AKIBAT PERCERAIAN DI KABUPATEN SLEMAN - Prawita, Deliananda; Agusta, Rivga (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
Closeness between families of teenage boys is one of the important things in family growth and development. Divorced families tend to have minimal relationships which affect children's life patterns and mental health. This leads to the goal to be achieved, namely the application of communication patterns and the character of teenage boys in psychological development. Also, we want to provide parents with an understanding regarding the importance of communication in a broken home family so that the impact obtained by teenagers can be good in the maturation process in all social environments. The theory of communication carried out by teenage boys with parents who are experiencing divorce is one-way or interpersonal communication. This research method uses qualitative and interview techniques to obtain results according to the requested subject. This interpersonal communication can be developed at different stages for each perpetrator and victim of parental divorce cases. The indicators parents and teenagers need are mentors, openness, empathy, feelings of security and support. Improving morals in this social environment can be discussed by several related parties so that teenagers can better develop feelings and mental health.